(untitled) (Indian Journal of Public Health Research & Development, 2020)
Objectives : The objectives of the study were 1.To assess the risk factors of Diabetic foot ulcer.2.To Find the associations between risk factors and Diabetic foot ulcer.3.To stratify the foot ulcer risk population among diabetes mellitus patients. Method: A Non-experimental descriptive research design was used in this study.133 clients were selected and explained the purpose of the study and consent was taken. The clients were interviewed by using questionnaires’ regarding risk factors of diabetic foot ulcer. Client who were interviewed through the questions were explained by the translator and the answers were marked immediately. The average time spend for every client is 15 minutes. Result: The result revealed that out of 133 samples 32% of 43 no. of diabetes mellitus people have inadequate knowledge , 61% of 81 no .of diabetes mellitus people have moderately adequate knowledge , 6.8% of 9 no. of diabetes mellitus people have adequate knowledge.